Ossifying fibroma: a case report - Taşar, Ferda; Giray, Celal Bahadır; Taşman, Uğur; Saysel, Mustafa Yiğit (The Turkish Journal of Pediatrics, 1996)
Ossifying fibroma is a benign tumor of connective tissue origin which occurs in fibro-osseous lesions. The lesion is seen most commonly in children and young adults. It is asymptomatic and slow-growing, but in some cases may show aggressive behavior. Though it has a slight predilection for the mandible, it may involve both jaws. The lesion is generally asymptomatic until it produces noticeable swelling, and mild deformity and migrations of teeth may be an early clinical feature. Pediatricians and dentists must be aware when asymmetry of the face occurs, and the lesion must be well diagnosed as it has a cancer-like radiographic appearance. In this article a nine-year-old patient with a massive mandibular ossifying fibroma is presented.